IMPLEMENTATION OF C4.5 ALGORITHM IN CLASSIFYING BREAST CANCER BASED ON MENOPAUSE AGE - Dari, Wulan; Miranda, Nisrina (LPPM Universitas Nusa Mandiri, 2021)
Breast cancer is a malignant tumor that can attack breast tissue, is a disease that is most feared by women. Although based on recent findings not only women are affected by breast cancer, it turns out that men can get breast cancer, although it is still very rare. Breast cancer is one type of cancer that is often experienced by women in Indonesia. Data mining is a process that uses statistical, mathematical, artificial intelligence and machine learning techniques to interact and identify useful information and related knowledge from large databases. Breast cancer is much feared by women as well as young and old age which can lead to death, if as early as possible for a full examination, this lump initially shrinks, but over time it enlarges, then sticks to the skin or causes changes in the skin of the breast (nipple). But the skin or nipple is pulled inward (retraction), light redness, or browning, until swelling, shrinking or sore breasts get worse the old ones will get bigger and deeper so that they can crush the one breast often smells bad and bleeds easily . C4.5 algorithm and decision tree are two inseparable models, because to build a decision tree, C4.5 algorithm is needed. Decision trees are one of the most popular classification methods because they are easy for humans to interpret. A decision tree is a predictive model using a tree structure or hierarchical structure. The concept of a decision tree is to convert data into a decision tree and decision rules.